Designing PAS (Passive Active Structure) Application based on an Android for Eleventh Grade Students of SMA Islam AT- Taufiq Diwek Jombang - Afidah, Nurul; Nugraha, Rizky Aditya; Nur, Luluk Choirun Nisak (Universitas KH. A. Wahab Hasbullah, 2022)
This research aims at designing PAS (Passive Active Structure) based on an Android Application in Grammar lesson for 11th-grade students of AT- Taufiq Islamic Senior High School, Diwek, Jombang. The research used Research and Development method (R&D) that the researcher adapted from ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Taken from the data on the development phase, the researcher obtained a result of 100% points on media validation that was categorized as “good quality”. The result of material validation is 70,8% points that were also classified as “good quality”. Moreover, in the implementation phase, the student's responses were 76,8% that could be classified as